Information hiding interfaces for aspect-oriented design. - Sullivan, Kevin (Software engineering notes.)
The growing popularity of aspect-oriented languages, such as AspectJ, and of corresponding design approaches, makes it important to learn how best to modularize programs in which aspect-oriented composition mechanisms are used. We contribute an approach to information hiding modularity in programs that use quantified advising as a module composition mechanism. Our approach rests on a new kind of interface: one that abstracts a crosscutting behavior, decouples the design of code that advises such a behavior from the design of the code to be advised, and that can stipulate behavioral contracts. Our interfaces establish design rules that govern how specific points in program execution are exposed through a given join point model and how conforming code on either side should behave. In a case study of the HyperCast overlay network middleware system, including a real options analysis, we compare the widely cited oblivious design approach with our own, showing significant weaknesses in the former and benefits in the latter.